2016
DOI: 10.2298/tsci16s4127m
|View full text |Cite
|
Sign up to set email alerts
|

Production of gaseous fuel from jatropha oil by cerium oxide based catalytic fuel reactor and its utilisation on diesel engine

Abstract: a De part ment of Au to mo bile En gi neer ing, Dr. Mahalingam Col lege of En gi neer ing and Tech nol ogy, Pollachi, In dia b De part ment of Me chan i cal En gi neer ing, Dr. Mahalingam Col lege of En gi neer ing and Tech nol ogy, Pollachi, In dia c De part ment of Me chan i cal En gi neer ing, Annamalai Uni ver sity, Chidambaram, In dia d De part ment of Me chan i cal En gi neer ing, Gov ern ment Poly tech nic Col lege, Coimbatore, India Orig i nal sci en tific pa per

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…As this tool is 1-D simulation tool, the time frame required for the simulation is negligible. Thus it reduces time and cost involved and helps to predict results with fair accuracy [10]. The dual fuel capabilities of the diesel engine will reduce the dependency on fossil fuels [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…As this tool is 1-D simulation tool, the time frame required for the simulation is negligible. Thus it reduces time and cost involved and helps to predict results with fair accuracy [10]. The dual fuel capabilities of the diesel engine will reduce the dependency on fossil fuels [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The uncertainty analysis was performed based on the list of measurement uncertainties of various equipment's used in this study are shown in tab. 3 and the total uncertainty was found to be ±2.79% [1]. Table 2.…”
Section: Experimental Set-upmentioning
confidence: 92%
“…Energy is one of the basic requirements for economic development of a country. The consumption of energy has been increased day by day and becoming more dependent on depleting fossil fuels in the world [1,2]. Rising cost of fossil fuels and related environmental issues pose greater threat to sustained economic development.…”
Section: Introductionmentioning
confidence: 99%